Pokdarwis (Kelompok Sadar Wisata) dan Kualitas Sumber Daya Manusia (SDM) di Desa Carangwulung Dalam Pengelolaanwisata Alam Grojogan Selo Gonggo - Ramadhan Eka Syahputra Nurhidayat; Wahyu Fahrul Ridho (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The tourism potential in Carangwulung Village is very diverse and has the potential to be developed into an attractive tourist object. There are eight tourist destinations developed in Carangwulung Village, one of which is Grojogan Selo Gonggo (GSG), a natural tourist destination that offers the beauty of mountain water and pine forests. The potential for tourism activities at GSG is very promising, especially if the local community and managers work together to achieve the expected goals. However, over time, the people involved in managing the GSG experienced a decrease in awareness of the importance of the tourism aspect. Therefore, it is important to increase tourism awareness for the people of Carangwulung Village so that the development of nature tourism at GSG is not in vain and can provide maximum benefits from tourism activities.Â The research method used in this study is a descriptive approach based on direct data collection by researchers from objects observed in the field, thus enabling analysis of existing problems and formulation of solutions. The main goal is to make GSG a tourist destination that is in demand by many tourists.Â